Guest Editorial Introduction to the Special Section on Recent Advances on Absorbers/Rasobers and Their Applications on Antennas and EMC - Peng Mei; Ahmed Abdelmottaleb Omar; Bo Li; Shuai Zhang; Wonbin Hong (IEEE Open Journal of Antennas and Propagation)
Four articles have been accepted for publication in this special section on “Recent Advances on Absorbers/Rasobers and Their Applications on Antennas and EMC”. These articles cover four distinct topics: microwave absorbers, radar cross-section reduction through phase distribution across metasurfaces, the design of miniaturized rasobers, and the 3D microwave absorber with wide angular stability. In the first article, Ning et al. [A1] provide a design methodology based on characteristic mode analysis to design reconfigurable microwave metasurface absorbers. A broadband absorber design was reported with a step-bystep process, which was verified by a full-wave simulation and measurement of a fabricated prototype. A bandwidth of 105% from 3.6 to 11.6 GHz was accomplished with less than -10 dB reflection coefficient. In the second article, Al-Nuaimi et al. [A2] utilize a novel cusp phase distribution across metasurface to achieve radar cross-section reduction. Without the need for lengthy optimization, it was found that the cusp phase mask was able to achieve radar crosssection reduction of more than 10 dB over a bandwidth of 81.8%. A stable performance was accomplished under both the normal and oblique incidence up to 75°. In the third article, Zargar et al. [A3] propose a miniaturized rasorber design with dual transmission bands within a wide absorption band. A design flow of the proposed rasorber was presented to give an overview of the design process. The final design exhibits a wide absorption band from 3.7 to 14.6 GHz and two transmission bands were generated within that band at 10.7 GHz and 16 GHz with insertion losses of 1 and 0.7 dB, respectively. The simulated results were confirmed by a fabricated prototype and measurements. In the last article, Feng et al. [A4] propose universal equivalent transmission line (TL) model and design method for efficient absorption under large angles to synthesis the absorptive performance of an absorber. A prototype with 70° angular stability is designed as an example to validate the proposed methods, where the measurements agree well with the synthesized and simulated results. Specifically speaking, the measured average absorption ratios (ARs) under normal incidence, 45° incidence, and 70° incidence are 94.2%, 94.0%, and 92.3%, respectively.